1990
DOI: 10.3109/02841859009177481
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Non-Enhanced, Bolus Enhanced, and Delayed Scanning Techniques in Computed Tomography of Hepatic Tumours

Abstract: Non-enhanced, bolus contrast medium enhanced and 4 to 6 hours delayed computed tomography of the liver was performed in a prospcctivc study of 53 patients. Forty patients had focal lesions, in 12 of these they were hypervascular. Contrast medium was administered as an initial bolus followed by a rapid injection of meglumine metrizoate (Isopaque Cerebral). The total iodine dose varied between 56 and 63 g, which gave an average increase in attenuation of 14 HU in normal parenchyma comparing delayed with nonenhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…During an investigation of hepatic focal lesions at delayed CT we observed that many patients had contrast medium in the biliary tract (19). The examinations were reviewed in order to decide the extent and diagnostic value of biliary tract opacification.…”
mentioning
confidence: 99%
“…During an investigation of hepatic focal lesions at delayed CT we observed that many patients had contrast medium in the biliary tract (19). The examinations were reviewed in order to decide the extent and diagnostic value of biliary tract opacification.…”
mentioning
confidence: 99%